EKSPERIMENTASI MODEL PEMBELAJARAN NHT DAN SNOWBALL THROWING PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP AL-NUR CIBINONG - Kusuma, Arie Purwa; Susanty, Irma (Jurnal Pendidikan Matematika dan IPA, 2019)
AbstractThe aim of the research was to find out the effect of learning models on mathematics achievement. The learning model compared were NHT(Numbered Head Together), snowball throwing and convensional. The type of the research was a quasi-experimental by 3Ã—1 factorial design. The population was the eight grade student of junior high school in Cibinong district on academic year 2017/2018. The sampling tecnique was cluster random sampling. The size of the sampel was 103 students consisted of 36 students in the first experimental group, 34 Â students in the second experimental group and 33 students in third experimental group. The instruments used were mathematics achievement test. The data was analyzed using unbalanced one-way analysis of variance. The conclusions of the research was NHT learning model gives better mathematics achievement than Snowball Throwing and convensional learning model, and snowball throwing learning model give better mathematics achievement than convensional learning model.Keywords: NHT, Snowball throwing, mathematics achievement